A influência da hora do dia sobre o desempenho físico, as funções executivas e as respostas fisiológicas de atletas de voleibol de alto rendimento - Gabriela Cangussú Felício dos Santos Monteiro de Castro (2017)
Time of the day can influence athlete`s performance of during physical activity and the optimal time for improved sports performance will depend on the type of activity to be performed, along with the impact of their components (physical/cognitive) on overall performance, since these components reach their peak at different times of day. The influence of a biological clock in addit in to our lifestyle can make the difference between success and failure in sports. Thus, aim of this study was to verify the influence of the time of day on performance (jump height, agility and running distance) an the executive functions and physiological variables (blood glicos and lactate, heart rate and internal temperature) of high-level volleyball players. Fourteen male volleyball athletes performed the experiment at two different times, in the morning (8:00 a.m. - 10:00 a.m.) and in the evening (6:00 p.m. - 8:00 p.m.). For the evaluation of physical performance were performed: countermovement jump, squat jump, Shuttle Run and Yo-Yo test and to evaluate the executive functions the FIVE DIGITS test was applied. The results indicate that the performance on squat jump, agility test and Yo-Yo maximum progressive test was greater in the evening compared to the morning (6.67%, 3.47%, 1.45% and 6.9%, respectively). The executive functions and the physiological variables did not present significant differences between morning and evening. A circadian variation was observed in the subjective mood state, showing greater vigor and less fatigue in the evening, when compared to the morning. These data suggest that jump height, agility, running distance and mood states are influenced by the time of day. However, executive functions and physiological variables did not present circadian variations, but may be influenced by previous exercise